Factores biosocioculturales y nivel de satisfacción materna en la discontinuidad al control de crecimiento y desarrollo preescolar - Monzón Rosado, Rosa (2017)
The present correlational descriptive, cross - sectional research, was carried out at the San Martin de Porres health center in Trujillo – 2017; which the finality of determine the relationship between Biosociocultural Factors and Maternal Satisfaction level in Discontinuity to Control of Growth and Preschool development. The sample consisted of 191 mothers of preschool children. Two instruments were used for data collection: a record sheet on growth and development control of preschool and the questionnaire on biosociocultural factors and level of maternal satisfaction, both elaborated by Rubio and Salazar (2013) and Mendizábal (2015). The obtained information was processed and analyzed in the SPSS program version 21 and presented in tables of single and double entry, to determine the relationship between the variables was used the Chi square statistical test (X2). Concluding that: of the total of mothers 63% discontinued and 36.6% presented continuity to the control. There is a significant relationship between the maternal biosociocultural factor: Level of knowledge and the level of maternal satisfaction and discontinuity to the control of growth and development in preschool. KEY WORDS: Biosociocultural factors; Maternal Satisfaction; Discontinuity, growth and development, preschoolers